Therapeutic Relationship, Play and the Approach of the Sexual Abuse Experience in Psychotherapy: The Perspective of Children and Adolescents - Madrid Ríos, Myriam; Rodríguez, Loreto; Capella Sepúlveda, Claudia (Revista de Psicología, 2022)
This study aimed to learn the experience of children who have been victims of sexual abuse, about their psychotherapeutic processes. Based on a qualitative approach, data were collected by in-depth interviews carried out with ten children and adolescents aged seven to 14 years old, who started their therapies in their school years. Data was analysed using a narrative approach. The results show that children appraise the psychotherapy as positive, evaluating it as a source of significant support. Furthermore, participants identify the diverse aspects that influence their psychotherapy experiences, such as the therapeutic relationship, play, and approaching the sexual abuse topic in therapy. From the perspectives of children, these three aspects would favour the process of healing from the sexual abuse experience. This study’s findings allowed us to explore psychotherapy experiences from the narratives of children, a field scarcely studied. Finally, implication from the results of this study for the clinical and psychosocial interventions with children who have lived through sexual abuse experiences are discussed.